IL-15 and IL15RA in Osteoarthritis: Association With Symptoms and Protease Production, but Not Structural Severity - Warner, Sophie C.; Nair, Anjali; Marpadga, Rahul; Chubinskaya, Susan; Doherty, Michael; Valdes, Ana M.; Scanzello, Carla R. (Frontiers in Immunology, 2020)
Objective: Interleukin-15 (IL-15) is a pro-inflammatory cytokine that is increased in joint fluids of early-stage osteoarthritis (OA) patients, and has been associated with expression of proteases that can damage cartilage, and the development of neuropathic pain-like symptoms (NP) after nerve injury. The objective of this study was to further explore the role of IL-15 in the pathogenesis of OA cartilage degeneration and test genetic variation in the IL-15 receptor α gene (IL15RA) for an association with OA with radiographic severity and symptoms. Methods: Cartilage samples from donors (n=10) were analysed for expression of the IL15 receptor α-chain using immunohistochemistry, and for responses to IL-15 in vitro using explant cultures. Data from two independent Nottinghamshire-based studies (n=795 and n=613) were used to test genetic variants in the IL15RA gene (rs2228059 and rs7097780) for an association with radiographic severity, symptomatic versus asymptomatic OA and NP. Results: IL-15Rα was expressed in chondrocytes from cartilage obtained from normal and degenerative knees. IL-15 significantly increased the release of matrix metalloproteinase-1 and -3 (MMP -1 and -3), but did not affect loss of proteoglycan from the articular matrix. Genetic variants in the IL15RA gene are associated with risk of symptomatic versus asymptomatic OA (rs7097780 OR=1.48 95% 1.10-1.98 p<0.01) and with the risk of NP post-total joint replacement (rs2228059 OR=0.76 95% 0.63-0.92 p<0.01) but not with radiographic severity. Conclusions: In two different cohorts of patients, we show an association between genetic variation at the IL15 receptor and pain. Although ex vivo cartilage explants could respond to IL-15 with increased protease production, we found no effect of IL-15 on cartilage matrix loss and no association between IL15RA variants and radiographic severity. Together, these results suggest that IL-15 signalling may be a target for pain, but may not impact structural progression, in OA.